Audit independence and customer relationship marketing: an ethical conflict or an ethical mutual effect? - Martins, Gabriel G.; Casais, Beatriz (Journal of Business Economics and Management, 2024)
Independence in financial auditing is a topic with extensive research, due to the ethical values expected from accountants and the conflicts with agency pressures and commercial interests. However, there is a lack of research on the benefits of ethical behaviors in the dynamic interactions between auditors and clients. This study aims to achieve through a qualitative approach an in-depth understanding of the self-perceived auditor independence and how it intervenes in the relationship with clients. Ten semi-structured interviews with auditors from the five major audit offices in the city of Porto were conducted. The results explore conflicts of interest between auditor independence and customer relationships. However, the findings highlight that improving auditor’s independence allows at the same time the development of a better professional relationship with the client, mitigating the conflicts of interests identified in previous literature. This paper presents a formula in which audit firms can leverage the concept of independence when they promote communication, transparency, and an open market. Regulation and supervision should work in favour for the same goal.